En sag af principiel karakter. Om at definere religion. - Schaffalitzky de Muckadell, Caroline (Religionsvidenskabeligt Tidsskrift, 2015)
This article argues that a more systematic approach to defining religion is needed. The starting point of the article is a case in which a soccer fan club applied for official recognition as a religious denomination. The fan club’s application was rejected, but without stating the criteria which it failed to meet in order to be considered religion. The example suggests that it is still relevant to raise questions both about whether scholars of religion ought to try to define religion, and about how such a case should be handled. This article presents a philosophical-methodological approach to the task of defining religion and it outlines a proposal for a definition based on this method. So, in addition to putting an earlier, well-known discussion and a more recent suggestion in perspective, the article suggests criteria which could have substantiated a rejection of the soccer fan club’s application.